Respiratory support strategies in the management of severe, longstanding bronchopulmonary dysplasia - Logan, J. Wells; Nath, Sfurti; Shah, Sanket D.; Nandula, Padma S.; Hudak, Mark L. (Frontiers in Pediatrics, 2022)
ABSTRACT Despite efforts to minimize ventilator-induced lung injury, some preterm infants require positive pressure support after 36 weeks’ post-menstrual age. Infants with severe BPD typically experience progressive mismatch of ventilation and perfusion, which manifests as respiratory distress, hypoxemia in room air, hypercarbia, and growth failure. Lung compliance varies, but lung resistance generally increases with prolonged exposure to positive pressure ventilation and other sources of inflammation. Serial lung radiographs reveal a heterogeneous pattern, with areas of both hyperinflation and atelectasis; in extreme cases, macrocystic changes may be noted. Efforts to wean the respiratory support are often unsuccessful, and trials of high frequency ventilation, exogenous corticosteroids, and diuretics are common. The incidence of pulmonary hypertension increases with the severity of BPD, as does the mortality rate. Therefore, periodic screening and efforts to mitigate the risk of PH is fundamental to the management of longstanding BPD in infants. Failure of conventional, lung-protective strategies (e.g., high rate/low tidal-volume and/or high frequency ventilation) warrants consideration of ventilatory strategies individualized to the disease physiology. Non-invasive modes of respiratory support may be successful in infants with mild to moderate BPD phenotypes. However, infants with moderate to severe BPD phenotypes often require invasive respiratory support, and pressure-limited or volume-targeted conventional ventilation may be better suited to the physiology than high-frequency ventilation. The consistent provision of adequate support is fundamental to the management of longstanding BPD and is best achieved with a stepwise increase in ventilator support until comfortable spontaneous respirations are achieved. Adequately supported infants typically experience improvements in both oxygenation and ventilation, which, if sustained, may arrest and generally reverses the course of a potentially lethal lung disease. Care should be individualized to employ strategies that address the most likely pulmonary mechanics, including variable lung compliance, elevated airway resistance, and variable airway obstruction.